Seni dan Simbolisme Budaya Masyarakat Kerinci dalam Batik Incung: Perspektif Sejarah - Nandia Pitri; Herwandi Herwandi; Lindayanti Lindayanti (PAMA Aksara, 2020)
This study revealed the phenomenon of incung batik as an art and cultural symbolism of the Kerinci community. The symbol on batik illustrates a community identity that is a non-verbal communication tool carried out by humans. The method used in this research is the method of historical research using the cultural approach and incung batik as its medium. The results showed that Kerinci was an area that was unique in developing batik motifs using the incung script (ancient Kerinci script). This is a cultural symbol for the people of Kerinci because they are able to develop ancient scripts by making it a batik motif. The art for the Kerinci community in batik is because the community can make batik with the development of incung batik and in the Kerinci community there is also a tradition of using batik cloth at weddings. Thus, batik usage in the Kerinci community has been going on since the past.